Hyaluronic acid-based levofloxacin nanomicelles for nitric oxide-triggered drug delivery to treat bacterial infections. (1st February 2020) - Lu, Chunbo; Xiao, Yao; Liu, Yinyin; Sun, Feifei; Qiu, Yuanhao; Mu, Haibo; Duan, Jinyou
Graphical abstract: Highlights: Levofloxacin conjugated hyaluronic acid was synthesized by o -phenylenediamine group linkage. HA-NO-LF nanomicelles could enter macrophages via a CD44 mediated endocytosis. HA-NO-LF nanomicelles showed better bactericidal effects against S. aureus than LF in vivo . Abstract: Antibiotics are powerful weapons to fight against bacterial infections, while most of them lack of selective targeting towards pathological site which could restrict their antibacterial efficacy. To overcome this challenge, an antimicrobial levofloxacin(LF)was conjugated onto hyaluronic acid (HA) moieties via an o -phenylenediamine linker to prepare a NO-sensitive nanosystem (HA-NO-LF) in this study. The HA-NO-LF nanomicelles could enter host cells via a CD44 mediated endocytosis and release drug gradually upon exposure to endogenous NO. Furthermore, the more promising therapeutic effect of the nanomicelles in ameliorating inflammatory levels was observed in a mouse pneumonia model than that of LF. These results suggest that the HA-NO-LF nanomicelles may exert potent curative effect in infectious diseases.